Exploring Online Physical Education Teaching: What Have We Done and What Have We Learnt? - Tagimaucia, Varanisese; D’Souza, Gerald Santhosh; Chand, Satish Prakash (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2024)
Engaging with physical education teachers who were compelled to integrate technology into their lessons during the COVID-19 pandemic is crucial to understanding how the pandemic has presented this ‘new normal’ circumstance. It is vital to gain insight into the initial experiences of physical education (PE) teachers who transitioned to online physical education (OLPE) teaching, as well as to identify potential areas for improvement in the future. This study investigated the perspectives of secondary school PE teachers on OLPE teaching during the COVID-19 lockdown, their professional development, online training opportunities and future perceptions. Using a mixed-methods approach, this study analysed data from 35 secondary school PE teachers in Fiji, using Google Forms to collect quantitative data and semi-structured interviews for qualitative data. The quantitative data was categorized by age, gender, school setting, qualifications, and teaching experience, while the qualitative data was analysed by themes. The study found that teachers struggled with OLPE due to lack of preparedness, poor Internet connectivity, and lack of emphasis on PE during lockdown. Despite their readiness, integrating technology remains challenging due to a lack of incentives, limited support, and fear of the unknown. The study emphasises the vital importance of technology in creating engaging and relevant PE experiences and recommends the provision of specialised resources, personalised curriculum guidance, and a change in teacher training institutions' paradigms to incorporate contemporary technological applications in PE.